Effect of Scapular Intensive Training on Functional Recovery of Upper Extremities in Early Stroke - Min JIANG; Lun LUO; Fan BAI; Wenyuan SU; Chaomou HE; Tao XIANG (康复学报)
Objective:To investigate the effect of scapular intensive training on the functional recovery of upper extremities in early stroke patients.Methods:A total of 60 patients with stroke who met the inclusion criteria were selected as study subjects. The patients were randomly divided into control group and scapula reinforcement group, with 30 patients in each group. The control group were treated with conventional medical therapy and routine rehabilitation training, and the scapula reinforcement group increased scapular intensive training on the basis of the control group,40 minutes each time, once daily,7 days per week, continuous treatment for 4 weeks. Fugl-Meyer upper eExtremity motor function rating scale, Hong Kong version of hemiplegic upper extremity functional test (FTHUE-HK) scale and modified Barthel index (MBI) score were used to evaluate upper limb function and activities of daily living in patients with stroke.Results:After 4 weeks of treatment, Fugl-Meyer upper limb motor function scores, FTHUE-HK scale scores, and MBI index scores were significantly higher than those before treatment in both groups, with statistically significant differences (P<0.05);and the scores of the evaluation scores of the scapular augmentation group were higher than those of the control group, with statistically significant differences (P<0.05).Conclusion:The scapula reinforcement group can improve the upper extremity motor function and the activities of daily living in stroke patients.